How Information Technology Investment Affects Green Innovation in Chinese Heavy Polluting Enterprises - Xiude, Chen; Yuting, Tan; Miaoxin, Lin; Guangyu, Zhang; Wencong, Ma; Shiwei, Yang; Yulian, Peng (Frontiers in Energy Research, 2021)
Promoting green innovation is an effective way to solve the increasingly serious environmental pollution problems in emerging economies. Information technology is constantly changing the operation mode of enterprises, however, whether information technology investment helps to promote enterprises’ green innovation is still an important issue to be studied. Based on resource-based and knowledge integration theory, this paper constructs data from Chinese A-share listed heavy polluting enterprises during 2010 to 2018, adopts panel data Tobit model to investigate the nexus between information technology investment and green innovation. Our empirical results demonstrate that the amount of information technology investment is positively correlated with the emerging levels of green patents in Chinese heavy polluting enterprises, and this positive correlation only significantly exists in state-owned enterprises, enterprises with strong sense of environmental responsibility and strict environmental regulation. The finds in this paper help us to understand in depth how information technology investment affect enterprises’ green innovation and its boundaries, which also have important policy implications for government departments and enterprises to make better use of information technology to deal with the challenge of environmental pollution.